The Development of Promissory Estoppel - Mohammad Matta, Ali (Journal of Malaysian and Comparative Law, 1999)
The obsession of the common law courts with the doctrine of consideration delayed the development of the equitable doctrine of promissory estoppel. Gradually, the courts realised the harshness which resulted from the indiscreet adherence to the requirement of consideration in contracts, in their making and discharge. Eventually, promissory estoppel was born.